Analysis of Health Level With Car Method to Investor Share Return Of Banking Companies in Indonesia Stock Exchange (Case Study at Indonesia State-Owned Banks in 2015-2020) - Yayah Sutisnawati; Muhamad Reza Muzaini (International Journal of Education, Information Technology, and Others, 2021)
Assessment of bank soundness using the Capital Adequacy Ratio (CAR) method is able to determine the state of a company's capital, because by looking at the CAR value investors can reduce losses and there are several previous studies that support CAR to have a positive effect on stock returns. However, what actually happened was that the soundness of state-owned banks using the CAR method on stock returns in 2015-2020 was not in accordance with the theory. This study analyzes the soundness of state-owned banks in terms of capital with a CAR ratio to investors' stock returns. The research method uses descriptive and verification methods using secondary data including the Capital Adequacy Ratio (CAR) and stock returns taken from the annual financial report data of each company and the IDX statistical annual report. The results of the research using descriptive method show that the capital element of each state-owned bank with a CAR ratio is in accordance with the provisions of Bank Indonesia. The results of the verification method show that the soundness of banks using the CAR method partially has a negative and insignificant effect on stock returns in the state-owned bank sector.